Landscape greening and local creation of wildflower strips and hedgerows promote multiple ecosystem services. Issue 2 (11th September 2017) - Sutter, Louis; Albrecht, Matthias; Jeanneret, Philippe
Abstract: The explicit and implicit aims of creating ecological focus areas (EFAs) and implementing greening measures in European agro‐ecosystems include the promotion of regulatory ecosystem services (ES) to sustain crop production in conventional cropping systems. However, the extent to which these goals are achieved with current policy measures remains poorly explored. We measured insect‐mediated pollination and natural pest control service provisioning in 18 winter oilseed rape fields as a function of the independent and interactive effects of local EFA establishment─sown wildflower strips and hedgerows─and landscape‐scale greening measures within a 1 km radius around focal fields and quantified their contribution to crop yield. Insect pollination potential and pest predation increased on average by 10% and 13%, respectively, when landscape‐scale greening measures share was increased from 6% to 26%. For pollination, the increase was stronger in fields adjoining an EFA (14%) than in fields without adjacent EFA (7%). Agricultural management practices were the main drivers of crop yield. Neither insect pollination potential or natural pest control (pest predation and parasitism) nor adjacent EFAs and landscape‐scale greening significantly affected crop yield in addition to agricultural management. Synthesis and applications . Local establishment of perennial, species‐rich wildflower strips and hedgerows, combined with landscape‐scale greening measures in agricultural landscapes, can promote multiple ecosystem services (ES) in conventional production systems. Benefits may be maximized when local and landscape measures are combined. However, enhanced pollination and natural pest regulation seem to contribute relatively little to final crop yield compared to local agricultural management practices in the high‐input conventional production system studied. Further research is needed to better understand how to improve the effectiveness of ecological focus areas and other greening measures in promoting regulatory ES. Potential improvements include minimising trade‐offs while promoting synergies between ES provision, food production and biodiversity conservation. Abstract : Local establishment of perennial, species‐rich wildflower strips and hedgerows, combined with landscape‐scale greening measures in agricultural landscapes, can promote multiple ecosystem services (ES) in conventional production systems. Benefits may be maximized when local and landscape measures are combined. However, enhanced pollination and natural pest regulation seem to contribute relatively little to final crop yield compared to local agricultural management practices in the high‐input conventional production system studied. Further research is needed to better understand how to improve the effectiveness of ecological focus areas and other greening measures in promoting regulatory ES. Potential improvements include minimising trade‐offs while promoting synergies between ES provision, food production and biodiversity conservation.